Mapping and navigation in an unknown environment using LiDAR for mobile service robots - Olvera Hale, Tomas (My University, 2020)
This paper presents the implementation of mapping, localization, and navigation algorithms for a mobile service robot in an unknown environment. The implementation uses a 3D LiDAR sensor to detect the environment and map an occupancy grid that allows global localization and navigation through the environment. The robot estimates the current position through the Monte Carlo localization algorithm with LiDAR sensor and odometry data. The navigation stack uses inflation to determine if the service robot can safely navigate through the environment, and avoid obstacles. Experimental results were considered using a simulated robot in an indoor environment without given prior knowledge of obstacles presented in the environment.
Keywords: Navigation algorithms; Service robot; Campus Ensenada